Three Cases of Crimean-Congo Haemorrhagic Fever from Eastern Anatolia - Guven, Tumer; Ustun, Cemal; Gozel, Mustafa Gokhan; Biten-Guven, Gulsum (Aves, 2010)
Crimean-Congo haemorrhagic fever (CCHF) is a viral zoonotic infectious disease with a high mortality rate. CCHF virus is a member of the Nairovirus genus of the Bunyaviridae family. Infection is transmitted to humans by tick bite or by direct contact with the blood or tissues of infected humans or viraemic livestock. CCHF is endemic in the Central and Northern Anatolia regions of our country. In this article, three cases of CCHF from Eastern Anatolia of Turkey were presented. All of the patients completely recovered with supportive treatment.
Do?u anadolu'dan üç Kirim-Kongo kanamali ateşi olgusu
Keywords: Crimean-Congo haemorrhagic fever; tick bite; zoonosis; Nairovirus; ribavirin